Modal analysis of thermal stress in aero-engine composite front body based on multifield calculation - Liu, Chao; Liu, Jingxian; Tang, Chenggang (Journal of physics. Conference series, 2025)
Aerodynamic heating reduces the structural mechanical performance of the aircraft engine, while also generating high temperatures and temperature gradients within the structure, leading to uneven thermal stress that affects the inherent dynamic characteristics of the structure. This paper focuses on the leading body at the inlet of the aircraft engine as the research subject. Based on a coupling algorithm, the uneven temperature field inside the leading body is obtained through flow field and heat conduction calculations. The temperature field is used as boundary conditions for calculating the stress field, and the thermal stress obtained is loaded onto the leading body for modal analysis with pre-stress. The study concludes with the first application of the fluid-thermal-structural multi-field coupling method to the thermal stress and modal analysis of ceramic nickel alloy composite materials: aerodynamic heating leads to a decrease in the inherent frequency of the composite material leading body, with the relative difference in the first five orders of natural frequency exceeding 5%. Particularly for the first-order vibration, the maximum difference can reach 10%. This makes the leading body more susceptible to resonance due to external disturbances, requiring consideration of the impact of aerodynamic heating on inherent frequency during design, with a focus on correcting the low-order inherent frequencies. The proposed calculation method has significant advantages in predicting the vibration performance of composite materials in extreme environments.